Comparison of Preemptive Post-Intubation 15 Mg/KgBW Paracetamol to 0.35 Mg/KgBW Meperidine in Incidence of Post-Anesthetic Shivering (Majalah Kedokteran Bandung, 2023)
Post anesthesia shivering (PAS) is a repetitive involuntary movement of one or more muscle groups as a result of a decrease in core body temperature. Pharmacological therapy in preventing PAS may include meperidine and paracetamol. This study compared the effectiveness of paracetamol to meperidine in reducing the incidence of post-anesthesia shivering. This study used an experimental randomized double-blind comparative analytic design on patients underwent exploratory laparotomy surgery under general anesthesia at Dr. Hasan Sadikin General Hospital Bandung, Indonesia, from September 2021 to August 2022. Patients with 50 ASA 1-2 physical status were included and divided into two groups. One group received 15 mg/kg group paracetamol and the other received 0.35 mg/kg meperidine. Data on tympanic membrane temperature and hemodynamics before and after induction and after extubating were collected. Furthermore, data on the results of the assessment of the incidence and grade of shivering in each treatment group were also collected. The results of this study showed that there was a decrease in the frequency of PAS in patients receiving intravenous 15 mg/kg paracetamol (p
Keywords: General anesthesia; meperidine; paracetamol; preemptive; shivering